Mycobacterium simiae pulmonary disease in Iran: systematic review and meta-analysis. (November 2018) - Nasiri, M.J.; Heidary, M.; Azimi, T.; Goudarzi, H.; Tabarsi, P.; Darban-Sarokhalil, D.; Feizabadi, M.M.
Abstract: Mycobacterium simiae is one of the most common nontuberculous mycobacteria (NTM) microorganisms causing lung disease in many countries in the world. A reliable estimate of the extent of M. simiae pulmonary disease has not been well investigated in Iran. We systematically searched multiple databases to identify relative studies. Studies were excluded if they did not use the American Thoracic Society (ATS) and Infectious Diseases Society of America (IDSA) diagnostic criteria for NTM diseases. Data were extracted independently and in duplicate. We assessed pooled estimate by using a random model effect, and sources of heterogeneity were assessed by using Cochran's Q and the I 2 statistic. The potential for publication bias was explored by using Begg's and Egger's tests. All analyses were conducted with Stata 14.0 (StataCorp, College Station, TX, USA). Of 172 articles identified, seven met the inclusion criteria. Of 355 patients who were culture positive for NTM, 82 had M . simiae pulmonary disease according to the ATS/IDSA diagnostic criteria. The pooled frequency of M. simiae pulmonary disease among patients with NTM was 25.0% (95% confidence interval, 16.8–33.2). No evidence of publication bias was observed among the included studies (p >0.05 for Begg's and Egger's tests). Clinical isolates of M. simiae are increasingly being recognized as a cause of pulmonary disease in Iran and need further attention by health authorities.